Analysis of Long-Range Transport of Carbon Dioxide and Its High Concentration Events over East Asian Region Using GOSAT Data and GEOS-Chem Modeling - Seung-Yeon Kim; Sang-Deok Lee; Jae-Bum Lee; Deok-Rae Kim; Jin-Seok Han; Kwang-Ho Choi; Chang-Keun Song (Advances in Meteorology)
This study aims to evaluate the long-range transport of CO2 in East Asian region, using concentration data in a surface measurement site (Gosan Station), column averaged concentration data of satellite-borne instrument (GOSAT), and GEOS-Chem modeling results for the period of June 2009 to May 2011. We perform a validation of the data from GOSAT and GEOS-Chem with total column observations (TCCON). The analysis of the long-range transport and high concentration (HC) events using surface/satellite observations and modeling results is conducted. During the HC events, the concentrations in CO2 and other air pollutants such as SO2 and CO are higher than that of all episodes. It means that CO2, known as a globally well-mixed gas, may also act as a fingerprint of human activity with unique regional characteristics like other air pollutants. This comprehensive analysis, in particular with GOSAT CO2 observation data, shows that CO2 plume with high concentration can be long-range transported with 1-2 days’ duration with regional scale. We can find out with GEOS-Chem tagging simulation that more than 45% of the elevated CO2 concentration over central/eastern China, Korea, and Japan on high concentration days can be explained by emission sources of East Asia mainland.